The Relation Between Clinical Phenotypes, GOLD Groups/Stages and Mortality in COPD Patients - A Prospective Multicenter Study - Brat, Kristian; Svoboda, Michal; Zatloukal, Jaromir; Plutinsky, Marek; Volakova, Eva; Popelkova, Patrice; Novotna, Barbora; Dvorak, Tomas; Koblizek, Vladimir (International journal of chronic obstructive pulmonary disease, 2021)
INTRODUCTION: The concept of phenotyping emerged, reflecting specific clinical, pulmonary and extrapulmonary features of each particular chronic obstructive pulmonary disease (COPD) case. Our aim was to analyze prognostic utility of: "Czech" COPD phenotypes and their most frequent combinations, "Spanish" phenotypes and Global Initiative for Chronic Obstructive Lung Disease (GOLD) stages + groups in relation to long-term mortality risk. METHODS: Data were extracted from the Czech Multicenter Research Database (CMRD) of COPD. Kaplan-Meier (KM) estimates (at 60 months from inclusion) were used for mortality assessment. Survival rates were calculated for the six elementary "Czech" phenotypes and their most frequent and relevant combinations, "Spanish" phenotypes, GOLD grades and groups. Statistically significant differences were tested by Log Rank test. An analysis of factors underlying mortality risk (the role of confounders) has been assessed with the use of classification and regression tree (CART) analysis. Basic factors showing significant differences between deceased and living patients were entered into the CART model. This showed six different risk groups, the differences in risk were tested by a Log Rank test. RESULTS: The cohort (n=720) was 73.1% men, with a mean age of 66.6 years and mean FEV1 44.4% pred. KM estimates showed bronchiectases/COPD overlap (HR 1.425, p=0.045), frequent exacerbator (HR 1.58, p<0.001), cachexia (HR 2.262, p<0.001) and emphysematous (HR 1.786, p=0.015) phenotypes associated with higher mortality risk. Co-presence of multiple phenotypes in a single patient had additive effect on risk; combination of emphysema, cachexia and frequent exacerbations translated into poorest prognosis (HR 3.075; p<0.001). Of the "Spanish" phenotypes, AE CB and AE non-CB were associated with greater risk of mortality (HR 1.787 and 2.001; both p=0.001). FEV1% pred., cachexia and chronic heart failure in patient history were the major underlying factors determining mortality risk in our cohort. CONCLUSION: Certain phenotypes ("Czech" or "Spanish") of COPD are associated with higher risk of death. Co-presence of multiple phenotypes (emphysematous plus cachectic plus frequent exacerbator) in a single individual was associated with amplified risk of mortality.
Keywords: classification and regression tree; CART; Španělsko; Female; Phenotype; Spain; chronická bronchitida; ženské pohlaví; chronic obstructive pulmonary disease; COPD; lidé; Pulmonary Disease, Chronic Obstructive; phenotypes; chronická obstrukční plicní nemoc; prospektivní studie; Male; progrese nemoci; Aged; Prospective Studies; Disease Progression; Bronchitis, Chronic; cluster; mortality; senioři; mužské pohlaví; fenotyp; Humans